Insecurity and Deprivation Impeding Citizens Education and Sustainable Development in Nigeria: The Psychosocial Factors Imperative - Okanezi, Bright; Amadi, Stella (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
Education is recognized the world over as a veritable tool for human capacity development. Nigeria shares in this idea hence a reasonable amount of money is budgeted annually for education sector, citizens also enroll in schools for acquisition of knowledge and skills for effective functioning in society. Unfortunately, Nigeria in recent years have been experiencing cases of insecurity and deprivation which impede citizens’ education. The paper discusses insecurity and deprivation as impediments to citizens’ education and sustainable development; and the psychosocial factors imperative. It was recommended among other things that psychosocial factors such as motivation, social interaction skills and environmental support should be emphasized; National Orientation Agency should foster the right types of attitude and values on students through enlightenment campaigns the government should rise up to the challenge of protecting lives and property; social security such as monthly allowances, bursaries, scholarships etc should be provided; professional guidance counsellors should be employed to counsel students. Keywords: Inequality, deprivation, citizens, students, education